Characterization and Evaluation of the Efficacy of Cationic Complex Mediated Plasmid DNA Delivery in Human Embryonic Palatal Mesenchyme Cells - D’Mello, Sheetal (J Tissue Eng Regen Med, 2014)
The purpose of this study was to develop and test a non-viral gene delivery system that can be employed to deliver genes of interest into a pre-osteoblastic cell line. Human embryonic palatal mesenchymal (HEPM 1486) cells were transfected with vector-plasmid DNA (pDNA) complexes. We explored calcium phosphate and polyethylenimine (PEI) as non-viral vectors and compared their respective in vitro transfection efficacies. Plasmid DNA encoding luciferase protein (LUC) was complexed with PEI (with differing N/P ratios) and calcium phosphate (with differing Ca/P ratios) using established protocols. The complexes prepared were then characterized for size and surface charge using a Malvern Zetasizer Nano-ZS. The transfection efficiency and cytotoxicity of the prepared complexes were evaluated in HEPM cells. The PEI-pDNA complexes over the whole range of N/P ratios were found to be < 160 nm in size while the calcium phosphate-pDNA complexes were relatively bigger. The PEI-pDNA complexes prepared at a N/P ratio of 10 were found to have maximum transfection efficiency at 4 h of treatment with minimal cytotoxicity. The highest transfection efficiency obtained with calcium phosphate-pDNA complexes (Ca/P 200) was nearly 12-fold lower than that obtained with PEI-pDNA complexes (N/P 10). Following this, transgene expression in the HEPM cells treated with complexes prepared at a N/P ratio of 10 was further examined using pDNA coding for enhanced green fluorescent protein (EGFP-N1) or therapeutically relevant platelet-derived growth factor B (PDGF-B). In conclusion, PEI was a more effective vector for delivering genes of interest to pre-osteoblasts than calcium phosphate.